The Influence Of Procurement Digital Capabilities, Collaborative Supply Chain Management And Operational Capabilities On Sustainable Business Performance Mediated By Competitive Advantage In Geothermal Energy Company Partners - Ridwan Afandi (Green Publisher Indonesia, 2024)
This study aims to analyze the effect of Procurement Digitalization Capability, Collaborative Supply Chain Management, Operational Capability through Competitive Advantage on Sustainable Business Performance at Geothermal Energy Company Partners. The method used in this research is quantitative method, where this research uses surveys and questionnaires distributed to vendors or partners of the Geothermal Energy Company as the object of research. The research sample was selected using purposive sampling with the acquisition of 115 respondents. This study uses data testing methods using validity and reliability tests on each variable studied. While the data analysis method used in this research is the Structural Equation Model (SEM) with AMOS software. The results showed that the direct relationship between the Procurement Digitalization Capability variable had a positive effect on Competitive Advantage. Collaborative Supply Chain Management variables have no positive effect on Competitive Advantage. While Operational Capability has a positive effect on Competitive Advantage and finally Competitive Advantage has a significant positive effect on Sustainable Business Performance. Based on the results of this study, it is recommended for further research to be able to develop research in different industries and with a broader scope.